The effect of the Banking Capital on Finance Fixed Assets of the Bank: An Applied Study on a Sample of Iraqi Private Banks (Journal of Accounting and Financial Studies ( JAFS ), 2019)
To the Banks capital several uses, including the protection of deposits and this was approved by the Basel Committee, And Finance long-term investments which intended to investment in fixed assets that are essential to the continuation of banking activity, Fixed assets not financed from the funds of the deposit, but the owner equity do this jop. the current research tries to prove the effect of banks capital on fixed assets for a sample of iraqi private banks (bank of baghdad and Iraqi middle east Investment bank), for the period from 2011 until 2014. The research concluded that the capital of bank of baghdad affect on his total fixed assets by (84%), and the capital of Iraqi middle east Investment bank affect on his total fixed assets by (72%), It is a positive and high Regression coefficients, recognized the assumptions of the research